Moving to an earnings-related parental leave system do heterogeneous effects on parents make some children worse off? - Katrin Huber (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Can moving to an earnings-related parental leave system influence children s well-being and are heterogeneous effects on parents carried over to the entire family, making special groups of children worse off than others? To answer this question, this study exploits a large and unanticipated parental leave reform in Germany as a natural experiment. By replacing a means-tested by an earnings-related system the reform affected different groups of families to a variable extent. I find significant negative effects on newborns personality, while 2-3-year-old children improve their basic life skills and language skills. The first effect is especially pronounced in families who would be subject to a non-positive change in the overall benefit amount compared to the pre-reform situation, the second one is rather driven by those coming out as the reform s winners.
Keywords: J13; J18; J22; 330